1972
DOI: 10.1121/1.1913042
|View full text |Cite
|
Sign up to set email alerts
|

Direct Estimation of Multidimensional Tonal Dissimilarity

Abstract: Magnitude estimates were obtained for the dissimilarity of pure tones varying in frequency and intensity. In Expt. 1, a spatial embedding for a set of seven tones was determined by assuming the magnitude estimates represented distances in a two-dimensional space whose coordinate axes were pitch and loudness. Embeddings were determined for both Euclidean and "city-block" distance functions. A linear relation was consistently observed between the projections of the tones on dimensions of pitch and loudness and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…A two-dimensional spatial configuration was determined from the average ranks, using the iterative technique described by Carvellas and Schneider (1972). The loci of the stimuli in this two-dimensional Euclidean space are represented by the squares in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A two-dimensional spatial configuration was determined from the average ranks, using the iterative technique described by Carvellas and Schneider (1972). The loci of the stimuli in this two-dimensional Euclidean space are represented by the squares in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In that case, the value of stress (an index of the degree of nonmonotonicity) will be high and the obtained configuration will not accurately reflect the true configuration (Young, 1970). The high stress values found in both Carvellas and Schneider (1972) and Chipman and Carey (1975) indicate that this may, indeed, have been the case. Consequently, it would seem reasonable to employ a scaling technique that would not require that subjects generate numbers to represent dissimilarities.…”
mentioning
confidence: 99%
“…In fact, two previous studies have indicated that only two dimensions may be necessary to represent tonal dissimilarity. Carvellas and Schneider (1972) found that a two-dimensional auditory space with loudness and pitch as dimensions was able to account for magnitude estimates of the dissimilarity of pure tones varying in frequency and intensity. Chipman and Carey (1975) also found that a twodimensional auditory space could account for magnitude estimates of the dissimilarity of narrow-band noises varying in intensity and center frequency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the ranks were averaged across the two experiments to arrive at a representative rank order of color difference for the 55 pairs of 630-nm lights that differed in colorimetric purity. This average rank order served as input to a nonmetric scaling program (Carvellas & Schneider, 1972) which determined the best one-dimensional representation for the 11 stimuli. Stress (Kruskal, 1964) for this configuration was 6070.…”
Section: Resultsmentioning
confidence: 99%